2017
DOI: 10.1002/term.2386
|View full text |Cite
|
Sign up to set email alerts
|

Full-thickness oesophageal regeneration in pig using a polyurethane mucosal cell seeded graft

Abstract: Malignant oesophageal pathology typically requires resection of a portion of oesophagus. The aim of this study was to investigate attachment and growth of swine oesophageal mucosal cells on electrospun synthetic nanofibre matrices of varying chemistries and to determine whether a mucosal-seeded graft, in a swine animal model, could induce regeneration. Swine mucosal oesophageal cells were isolated and seeded them onto five different matrix materials. Matrix samples were cultured for up to 14 days, after which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…In the last few years, tissue engineering (TE) has emerged as a promising solution for the replacement of physiological esophageal functions [7][8][9]. This field of science has deeply benefited from meaningful progresses in biomaterial science, nanotechnologies, bioreactor technology, molecular biology, and stem cells discovery [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, tissue engineering (TE) has emerged as a promising solution for the replacement of physiological esophageal functions [7][8][9]. This field of science has deeply benefited from meaningful progresses in biomaterial science, nanotechnologies, bioreactor technology, molecular biology, and stem cells discovery [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal epithelial cells (EECs) are another cell source that can be easily obtained by endoscopy and used to seed the intraluminal surface of a scaffold. Many studies have utilized mucosal cells as a cell source in conjunction with various types of matrices [28][29][30][31][32]. These studies demonstrate epithelial regeneration when seeded scaffolds are used, while epithelia regeneration was absent in the absence of cells.…”
mentioning
confidence: 99%
“…These studies describe regeneration of the esophagus in up to 4 weeks with the presence of an epithelial layer and a disorganized or absent muscle layer. However, more recent studies using silk scaffolding [39][40][41], Poly lactic-co-glycolic acid (PLGA) [42,43], and polyurethane (PU) [28] describe smooth muscle and fibroblast regeneration followed by a squamous epithelial lining. The second objective of this study was to evaluate the feasibility of bridging a long intrathoracic esophageal gap with either an autologous EEC seeded or AF-MSC seeded polyurethane (Biostageâ„¢) graft in a porcine model of esophageal loss.…”
mentioning
confidence: 99%
“…Those difficulties mainly arise from the immunogenicity and low biocompatibility of the materials [17]. In recent years, each technology has gradually developed, and good research results have come to emerged [18–21]. Among them, in the report of decellularized esophagus, Guillaume et al reported that they had transplanted and obtained long-term survival after recellularization of decellularized porcine esophagus, and it is said to be an excellent method in terms of strength and tissue compatibility [21].…”
Section: Discussionmentioning
confidence: 99%